PS30 The Joint Effect of Unemployment and Cynical Hostility on All Cause Mortality. (17th September 2012) - Christensen, U; Kriegbaum, MK; Rod, NR; Osler, MO; Lund, RL
Abstract : Background: Unemployment as well as hostility has been associated with mortality and morbidity. Hostility and socioeconomic position, including unemployment is highly associated. One of the hypothetical models on the relation between hostility, health and life context, states that hostility moderates the relationship between health problems and stressful conditions in the environment, such as unemployment. The aim of this study is to analyze the joint effect of labor market exclusion and hostility on all cause mortality. Methods: This study is based on The Danish Longitudinal Study on work, Unemployment and Health, a survey carried out in the Spring 2000 among a random sample of 40 and 50 year old men and women and an oversampled group of previously unemployed individuals. The survey included self-reported measures on employment, education, age and hostility, measured by the eight-item Cynical Distrust Scale. The exposure variable was: 1) employed-not hostile ; 2) employed - hostile; 3) unemployed- not hostile and 4) unemployed - hostile. Outcome was defined as all-cause mortality. We used Cox's proportional hazard regression model, with age as the underlying time scale and with entry time January 1st 2000. All individuals who reported not working due to illness at the time of the survey were excluded in the analyses. The joint effect of unemployment and hostility was assessed as departure from multiplicativity. Results: Employed men and women who were hostile did not have an increased mortality risk. Unemployed men had an increased risk of mortality even when they were not hostile HR=2.30 (95% CI, 1.27–4.16) and the joint effect of unemployment and hostility was higher than what would have been expected from their separate effects, HR=2.57 (95% CI, 1.50–4.42). Unemployed women did not have a significantly increased mortality risk if they were not hostile HR=1.35 (95% CI, 0.73–2.50), however, the joint effect of unemployment and hostility was higher than what would have been expected from their separate effects, HR=2.23 (95% CI, 1.17–4.24). Conclusion: The joint effect of unemployment and hostility is a novel finding, indicating that the health damaging consequences of unemployment are accentuated by hostility.